A new assessment mechanism of primary frequency regulation capability for a supercritical thermal power plant in deep peaking. Issue 2 (22nd November 2022) - Hong, Feng; Ji, Weiming; Liang, Lu; Song, Jie; Hao, Junhong; Du, Ming; Ren, Guorui; Du, Yanjun; Niu, Yuguang; Fang, Fang
Abstract: With the rapid development of renewable energy, the primary frequency control (PFC) is becoming more critical and significant to ensure the stability of the electrical power system. As the main role of PFC, the thermal power unit tends to in a wide operation interval, and the changes in PFC characteristics along with working conditions are inevitable. By decomposing and quantifying the dynamic energy conversion process, this paper proposes a novel mechanism to evaluate the PFC capability for the supercritical thermal power plants that covered 30%–100% of the rated load. In the mechanism, a refined steam turbine model is established to reflect the short‐term dynamic response of PFC by combining it with the coupling characteristics of the main steam valve and main steam pressure in the later phase. Meanwhile, as a new prior assessment index, the equivalent electricity has been put forward to quantify the PFC capability for the power plant. In a case study of a 600 MW supercritical power plant, the capacities of PFC under 30%–50% of the rated load are quantified for the first time. Comparison results between theoretical calculation and real PFC test show that the proposed PFC capability assessment mechanism has acceptable accuracy of 96.1%, which could be effective to assess the frequency response reserve and stability margin in the grid. Abstract : By decomposing and quantifying the dynamic energy conversion process, this paper proposes a novel mechanism to evaluate the primary frequency control capability for the supercritical thermal power plants that covered 30%–100% of the rated load.